Developing quantitative approaches to determine microbial colonisation and activity in mineral bioleaching and characterisation of acid rock drainage - Makaula, Didi Xhanti (Centre for Bioprocess Engineering Research, 2020)
Colonisation of mineral surfaces by acidophilic microorganisms during bioleaching is important for accelerating the extraction of valuable metals from mineral sulfide ores of varying grades through biohydrometallurgy. It also influences acid formation and mineral deportment from sulfidic waste rock generated in mining processes and is key to its comprehensive waste rock characterisation for acid forming potential. This study assesses mixed mesophilic microbial interactions with, and colonisation of, pyrite concentrates and pyrite bearing waste rocks. The assessment of these interactions was carried out in this study in a synergistic qualitative as well as quantitative manner, with a particular focus on heap bioleaching for metal extraction and on disposal of waste rock, the latter through the case of characterisation of ARD generation potential. Using the tools developed, both the course of colonisation and development of metabolic activity with time of colonisation, as well as their correlation with leaching performance were studied. Furthermore, specific operating parameters such as ore grade and irrigation rates were explored. Finally, the application of this knowledge in a characterisation study was explored. To achieve the set of tools required for this study, two quantitative techniques were refined to characterise these microbial-mineral interactions. In the first, an isothermal microcalorimetric (IMC) method was developed and optimised to determine microbial colonisation of mineral surfaces quantitatively as a function of surface area (m-2 ). Three IMC configurations were considered: colonised pyrite-coated beads submerged in fresh media; beads submerged in cell free leachate; and beads in an unsaturated bed, each in the IMC vial. The highest heat output was measured in the unsaturated bed (263.3 mW m-2 ). The consistency of heat produced by the colonising microorganisms was determined through reproducibility studies. Using IMC, chemically and microbially facilitated pyrite oxidation rate studies were performed on unsaturated beds with varying surface area loadings, correlating to varying bead number. Results obtained showed similar normalised oxidation rates per surface area across the surface loadings. However, with more microbially colonised surface area loaded, the maximum heat generated was reached more quickly. This suggested that there was reagent (possibly O2) limitation in the system, which restricted microbial activity and its associated heat generation. Reagent limitation in the system was tested and validated through varying the O2 availability in the IMC vial by air displacement with CO2 and N2 gas, with the systems containing less O2 showing limited activity. Collectively the data showed that high activity, facilitated microbially, was achieved in unsaturated systems in a reproducible manner. Secondly, oxidation rates were determined and O2 limitation in the system was overcome. This then fundamentally informed the determination of activity from microbial-mineral interaction, using IMC, as a function of surface area. Secondly, a detachment protocol developed at UCT to recover microbial cells from surfaces of crushed and agglomerated ore to assess microbial growth rates and distribution in the ore bed, including cells in the interstitial phase and those weakly and strongly attached to the ore surface, was refined to assess colonisation of the finely milled pyrite-bearing concentrate or waste rock coated onto glass beads in continuous flow assays. The detachment protocol was assessed quantitatively by measuring initial and residual microbial activity, as a function of wash number, using IMC, thus providing a new level of confidence in the method. Mineral surfaces were visualised using scanning electron microscopy (SEM) following detachment for qualitative assessment. These data, together with microscopic enumeration of detached cells with increased number of washes, allow refinement of the assay and showed that six washes provided reliable estimation of mineral associated microbial cells. Extracellular polymeric substances (EPS) produced in this process were extracted using crown ether and the capsular bound components analysed. The analysed components included lipids (4.2 %), iron (16.4 %), DNA (26.8 %), and total carbohydrates (28.5 %), which are typical components of EPS. The carbohydrate fraction was further resolved to trehalose (26.2 %), fructose (36.5 %) and galactose (37.3 %) sugar monomers. The analysed EPS components confirmed presence of the EPS secreted by cells colonising the mineral ore or waste rock surface in a flow-through system, and visualised via SEM. The microcalorimetric approach developed together with the refined detachment method were applied to samples from a flow-through mini-column system, used to simulate microbe-mineral contacting in a heap. Here, the colonisation of pyrite concentrate by a mixed mesophilic culture of iron and sulfur oxidising microorganisms was assessed progressively over 30 days. The progression of mineral colonisation in the mini-column system was monitored using a combination of IMC, scanning electron microscopy, detachment method and conventional wet chemistry measurements. We observed an increase in the heat output from the colonised surfaces of pyrite mineral concentrate caused by oxidative reactions facilitated by mineral-microbial biofilm. This confirmed that the attached microorganisms were metabolically active and facilitated ongoing mineral leaching through regeneration of lixiviants. Correlation was shown between number of cells detached from the mineral surface and the heat generated, with a constant heat output per cell observed until day 15 of operation. Thereafter, the measured heat generated per cell increased, suggesting reduced efficiency of cell detachment owing to increasing firm attachment, or the lack in separation of single cells embedded within EPS matrix (clumps observed under light microscope after detachment). Using IMC to quantify the activity of the residual microorganisms on the mineral surface following detachment, it was confirmed that >95% of activity was detached through this protocol, hence the lower detached cell numbers determined following EPS formation were attributed to clumping of the detached cells. This correlated to an increased presence of EPS and was supported by SEM observation. Following the study of pyrite concentrate, colonisation of two pyrite bearing waste rock samples was assessed, with simultaneous establishment of the flow-through mini column biokinetic test configuration that resembles open flow in the waste rock dump. The flowthrough configuration was run alongside the refined UCT-developed batch biokinetic test using suspended mineral. In this study, two pyritic waste rock samples, liberated by milling, were characterised using three biokinetic test approaches: the slurry batch test (BT), the batch test using mineral-coated beads (BT-CB) and flow-through column test with mineral-coated beads (FT-CB). Our results have shown through static tests, solution redox potential and pH analysis that both waste rocks were acid forming. Furthermore, it was demonstrated in the FT-CB system that microbial proliferation on the waste rock surfaces progressed with time such that oxidative exothermic reactions facilitated by the increasing microbial presence on the surfaces were demonstrated using Isothermal microcalorimetry. This study presents and informs the on-going refinement of the biokinetic test through establishment of a flow-through test for ARD characterisation while providing insight into the role of the microbial phase in ARD generation. Microbial-mineral association was assessed under various operating conditions, including two solution flow rates (60 and 4 ml h -1 ) and minerals of varying sulfide content, including a pyrite concentrate (96 % pyrite), a high sulfide waste rock (33 % pyrite) and a low sulfide waste rock (14 % pyrite). Mineral grade impacted the activity of mineral associated microorganisms with higher activities observed on a mineral surface with high sulfide content. The activity measured from microorganisms that were associated with the pyrite concentrate was 827 mW m-2 at a 60 ml h -1 flow rate, whereas activity measured on low and high sulfide waste rock (PEL-LS and PEL-HS) were 293 mW m-2 and 157 mW m-2 respectively operated on the same flow rate. On decreasing the flow rate to 4 ml h -1 , the activity of microbial cells on PEL-LS and PEL-HS were 153 mW m-2 and 146 mW m-2 respectively. This study showed that the growth of microbial cell numbers coupled with metabolic activity is important to facilitate accelerated dissolution of sulfidic mineral surfaces. The rate of oxidation increased in the presence of EPS and thus EPS was further analysed, and its composition was confirmed. Overall, this study contributed to the understanding of microbial colonisation of mineral surfaces in a non-destructive quantitative manner. This study thus demonstrates the ability to measure and track both the growth and activity of microorganisms that are associated with mineral surfaces. This is important as it provides an approach to understanding microbe mineral surface interactions and, therefore, potential strategies to increase microbial colonisation of low-grade minerals that house valuable metals, during commercial heap bioleach processes. Furthermore, the ability to monitor progressive growth and activity of mineral associated microbial communities within a flow-through biokinetic test, as successfully demonstrated in this study, has the potential to significantly enhance current management of mine waste materials and ARD mitigation strategies. Therefore, on-going investigations of progressive microbe-mineral interactions will continue to be valuable both in terms of bioleaching for metal recovery and the mitigation of ARD through effective characterisation of mine waste material.